Experimental cross-species infection of donkeys with equine hepacivirus and analysis of host immune signatures - André Gömer; Christina Puff; Birthe Reinecke; Stephanie Bracht; Maria Conze; Wolfgang Baumgärtner; Jörg Steinmann; Karsten Feige; Jessika M. V. Cavalleri; Eike Steinmann; Daniel Todt (BMC, 2022)
Abstract Background The Equine Hepacivirus (EqHV) is an equine-specific and liver-tropic virus belonging to the diverse genus of Hepaciviruses. It was recently found in a large donkey (Equus asinus) cohort with a similar seroprevalence (30%), but lower rate of RNA-positive animals (0.3%) compared to horses. These rare infection events indicate either a lack of adaptation to the new host or a predominantly acute course of infection. Methods In order to analyze the susceptibility and the course of EqHV infection in donkeys, we inoculated two adult female donkeys and one control horse intravenously with purified EqHV from a naturally infected horse. Liver biopsies were taken before and after inoculation to study changes in the transcriptome. Results Infection kinetics were similar between the equids. All animals were EqHV PCR-positive from day three. EqHV RNA-levels declined when the animals seroconverted and both donkeys cleared the virus from the blood by week 12. Infection did not have an impact on the clinical findings and no significant histopathological differences were seen. Blood biochemistry revealed a mild increase in GLDH at the time of seroconversion in horses, which was less pronounced in donkeys. Transcriptomic analysis revealed a distinct set of differentially expressed genes, including viral host factors and immune genes. Conclusion To summarize, our findings indicate that donkeys are a natural host of EqHV, due to the almost identical infection kinetics. The different immune responses do however suggest different mechanisms in reacting to hepaciviral infections.